BIAYA KEMACETAN RUAS JALAN KOTA KUPANG DITINJAU DARI SEGI BIAYA OPERASIONAL KENDARAAN - Bolla, Margareth E.; Yappy, Ricky A.; Sir, Tri M. W. (Jurnal Teknik Sipil, 2017)
Congestion is one of unresolved problem in the major cities in the world, including in Indonesia. In Kupang City, including at Jend. Sudirman street, congestion happen at peak hours in the morning and afternoon. This study takes the case on two representative points at Sta. 00+750 and Sta. 01+418 and analysis for Vehicle Operating Costs (VOC) have done by per peak hour and then taken the average per point. Calculation of VOC refers to the similarities in Manual BOK 1995 method and LAPI ITB-PT. Jasa Marga method. Furthermore, by selecting the VOC, the largest from the two methods, are used to determine the amount of congestion cost per peak hour per vehicle by using the equation Tzedakis (1980). Based on the analysis, the result of VOC of Jend. Sudirman road is Rp. 8,938,-/hour for motorcycles (MC), Rp. 204,320,- /hour for vehicle car (LV) and Rp. 565,661,- /hour for heavy vehicles (HV), where bad Level of Service (LOS) happen at 6:30 to 7:30 pm, 09:00 to 10:00 am, 12:00 to 13:00 pm and 17:00 to 19:00 pm. In addition, total congestion costs is Rp. 723,241/vehicle/peak hour/trip